2011
DOI: 10.1007/s13131-011-0165-9
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of CO2-driven seawater acidification on survival, egg production rate and hatching success of four marine copepods

Abstract: Ecological experiments were conducted to examine the effects of seawater containing elevated partial pressure of carbon dioxide (p CO 2 800×10 −6 , 2 000×10 −6 , 5 000×10 −6 and 10 000×10 −6 ) on the survival and reproduction of female Acartia pacifica, Acartia spinicauda, Calanus sinicus and Centropages tenuiremis, which are the dominant copepods in the southern coastal waters of China. The results show that the effects of elevated p CO 2 on the survival rates of copepods were speciesspecific. C. sinicus, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…Recently, Weydmann et al (2012) reported that egg production of Calanus glacialis females was unaffected by a pH level of 7.6 and 6.9 but reduced hatching success was observed among the eggs that were incubated at the lowest pH level. Similar findings were observed for Calanus sinicus where no effect on adult survival and egg production rate was observed during an eight-day incubation period in seawater with a CO 2 level of up to 10000ppm (Zhang et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Recently, Weydmann et al (2012) reported that egg production of Calanus glacialis females was unaffected by a pH level of 7.6 and 6.9 but reduced hatching success was observed among the eggs that were incubated at the lowest pH level. Similar findings were observed for Calanus sinicus where no effect on adult survival and egg production rate was observed during an eight-day incubation period in seawater with a CO 2 level of up to 10000ppm (Zhang et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…Hessen & Nilssen, 1983;Stenson et al, 1993). Recently, copepod response to ocean acidification has been studied only during limited laboratory studies (Kurihara et al, 2004;Mayor et al, 2007;Kurihara & Ishimatsu, 2008;Zhang et al, 2011;Fitzer et al, 2012;Li & Gao, 2012;Mayor et al, 2012;Weydmann et al, 2012) demonstrating that the elevated CO 2 concentration in seawater has sub-lethal effects on copepods mainly, thus influencing vital rates, i.e. egg production, hatching success.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Weydmann et al (2012) reported that egg production in wild-caught Calanus glacialis (Jaschnov, 1955) females were unaffected by a pH level of 7.6 and 6.9 (corresponding to a pCO 2 of ∼ 1000 and ∼ 7000 ppm at the in situ temperature used, respectively), but a reduced hatching success was observed among the eggs that were incubated at pH 6.9. In wild-caught Calanus sinicus (Brodsky, 1962), no effect on adult survival and egg production rate was observed below 10 000 ppm CO 2 during an eight day long incubation period (Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As noncalcifying organisms, they are not directly affected by changes in Ω, and are predicted to be less vulnerable to pH perturbations than many other groups (Fitzer et al 2012). Several short-term laboratory studies have assessed copepod response to acute ocean acidification (Kurihara et al 2004, Mayor et al 2007, Kurihara & Ishimatsu 2008, Zhang et al 2011, Fitzer et al 2012, Li & Gao 2012, Mayor et al 2012, Weydmann et al 2012, Zervoudaki et al 2013). Results indicate a variety of sub-lethal effects, including de creased egg production, lower hatching success and a negative effect on excretion rates.…”
Section: Introductionmentioning
confidence: 99%